Isolation and characterization of bacteriophages specific to Streptococcus equi subspecies zooepidemicus and evaluation of efficacy ex vivo - Köhne, Martin; Hüsch, Ronja; Tönissen, Anna; Schmidt, Matthias; Müsken, Mathias; Böttcher, Denny; Hirnet, Juliane; Plötz, Madeleine; Kittler, Sophie; Sieme, Harald (Frontiers in Microbiology, 2024)
Streptococcus (S.) equi subspecies (subsp.) zooepidemicus is an important facultative pathogen in horses and can cause severe infections in other species including humans. Facing the post-antibiotic era, novel antimicrobials are needed for fighting bacterial infections. Bacteriophages (phages) are the natural predators of bacteria and discussed as a promising antimicrobial treatment option. The objective of this study was to isolate and characterize S. equi subsp. zooepidemicus-specific phages for the first time and to evaluate their efficacy in vitro and ex vivo. In total, 13 phages with lytic activity were isolated and host ranges were determined. Two phages with broad host ranges and high efficiency of plating (vB_SeqZP_LmqsRe26-2 (lytic activity: 30/37 bacterial isolates) and vB_SeqZP_LmqsRe26-3 (lytic activity: 29/37 bacterial isolates)) and one phage with relatively low efficiency of plating (vB_SeqZP_LmqsRe26-1) were selected for further characterization, including electron microscopy and whole genome sequencing. In in vitro planktonic killing assays at two tested multiplicities of infection (MOI 1 and MOI 10), significant bacterial growth reduction was observed when the phages vB_SeqZP_LmqsRe26-2 and vB_SeqZP_LmqsRe26-3 were added. These phages were subsequently co-incubated with clinical S. equi subsp. zooepidemicus isolates in an equine endometrial explant model but did not achieve bacterial growth reduction at MOI 1 and MOI 10. However, helium ion microscopy revealed presence of particles adherent to the bacteria on the explant after incubation (25 h), suggesting possible phage-bacteria interactions. In conclusion, phages against S. equi subsp. zooepidemicus were successfully isolated and characterized. Promising results were observed in in vitro but no significant reduction was detected in ex vivo experiments, requiring additional investigations. However, after further adaptations (e.g., optimization of MOIs and phage administration or use of phage-antibiotic combination), phages could be a potential antimicrobial tool for future therapeutic use in S. equi subsp. zooepidemicus infections, although the available results do not currently support the therapeutic usage.